Performance of doubled haploid lines in relation to those obtained by the conventional breeding method in tobacco - Lemos, Roxane do Carmo (2021)
In some species, the most used alternative to accelerate the process of obtaining lines is by using doubled haploids (DH). The existing question is whether the process of induction and duplication of chromosomes occurs randomly or there is a restriction in the segregation. If this fact occurs, it would be a restriction on its use since the variability generated in the crossings would not be fully explored. This work was carried out with the purpose to compare the performance of tobacco lines (Nicotiana tabacum L.) obtained by conventional breeding method (CM), with the obtained by the DH methodology, using anther culture. Additionally, to verify the feasibility of routine employment of DH in a recurrent selection program (RS). For this purpose, three populations of tobacco from the Virginia varietal group were obtained by biparental crossing. Considering all populations, the number of lines evaluated was 190 DH and 194 CM. They were evaluated simultaneously, in one experiment per population at two locations. The traits assessed were green leaf yield (YLD), total alkaloid content (ALK), and sugar content (SU). The genetic and the phenotypic parameters were estimated by population. It was found that: the performance of the DH in comparison to CM differed between the traits. For those related to quality, ALK and SU, the performance was similar. For YLD, the genetic variation estimates and h2, among the DH was higher than those of CM. However, the opposite occurred for the mean parameter. Considering all lines, regardless of the crossing, the CM mean was 13.3% higher than the DH mean, for YLD. Also, the annual gain with the selection was greater for CM to this trait. The use of DH in a SR program will be efficient in comparison to CM if a large number of DH are obtained which must undergo a preliminary selection before the most intensive evaluation to identify the lines to be recombined.